Functionalisation of Lignin-Derived Diols for the Synthesis of Thermoplastic Polyurethanes and Polyester Resins - Rachele N. Carafa; Justin J. S. Kosalka; Brigida V. Fernandes; Unnati Desai; Daniel A. Foucher; Guerino G. Sacripante (Molecules, 2025)
The functionalisation of lignin-derived phenolics (guaiacol, 4-propylguaiacol, eugenol, isoeugenol, phenol, m-cresol, catechol, syringol, syringaldehyde, and vanillin) for the synthesis of thermoplastic polyurethanes (PUs) and polyester (PE) resins is herein described. Diols were synthesised from phenolics in a one-step reaction using either glycerol carbonate or ethylene carbonate as a greener, solvent-free synthetic route. Nine of the diols were selected for the synthesis of Pus, and two of the diols were used for the synthesis of PE resins, with their physical and thermal properties characterised. Analysis of the PUs by differential scanning calorimetry (DSC) confirmed their amorphous nature, while thermogravimetric analysis (TGA) suggested improved thermal stability for all PUs with the addition of an alkyl or aldehyde substituent on the benzene ring regardless of the diisocyanate used. However, lower PU thermal stabilities were observed with the use of an aliphatic diisocyanate over an aromatic diisocyanate in the absence of an additional substituent. Analysis of the PEs by DSC also confirmed that the clear resins were all amorphous, and gel permeation chromatography (GPC) revealed significantly higher molecular weights and dispersities when an aliphatic diacid was utilised over an aromatic diacid.